Arthroscopic treatment of osteochondral lesions of the talus using platelet-rich fibrin biological scaffold - Baumfeld, Tiago Soares; Kuffner, Matheus; Macedo, Bruno Magalhães Gomes; Souza Junior, Eli Ávila; Macedo, Benjamim Dutra; Baumfeld, Daniel Soares (Journal of the Foot & Ankle, 2026)
Introduction: Osteochondral lesions of the talus (OLT) are a frequent cause of chronic ankle pain and functional limitation. Single stage biological strategies, such as autologous platelet-rich fibrin (PRF), have been proposed as scaffolds to enhance repair. Methods: This retrospective case series evaluated patients with symptomatic OLT treated arthroscopically with lesion preparation and application of an intraoperatively prepared autologous PRF scaffold (A-PRF membrane and i-PRF), with a minimum follow-up of 18 months. Outcomes included AOFAS, FAOS, and VAS scores, return to sports, and complications. Results: Thirty-six patients (14 women, 22 men; mean age 39 years) were included. AOFAS improved from 54.1 to 82.6 (p < 0.001), and VAS pain decreased from 7.58 to 2.69 (p < 0.001) at final follow-up. FAOS domains improved substantially, including quality of life (25.2 to 63.9). More than 80% of patients returned to sports at a mean of 7.6 months. The complication rate was 11.1%, including transient paresthesia, superficial wound infection, and one reoperation. Conclusion: Arthroscopic treatment of OLT augmented with an autologous PRF scaffold was associated with improved pain and function at mid-term follow-up with an acceptable complication rate. Comparative studies are needed to determine the incremental benefit of PRF over marrow stimulation alone.